The supramolecular structures of oximes: an update and the crystal structure of 1,3-diphenyl-propan-2-one oxime - John Nicolson Low (2010)
The crystal structure of 1,3‐diphenyl‐propan‐2‐one oxime, C15H15NO, is described. Thecompound crystallises in the monoclinic space group C2/c. Centrosymmetrically relatedmolecules are linked to form R22 (6) dimers. An update, since 2003, of a systematic analysisof the hydrogen bonding patterns in oxime structures with and without competitive O‐H...Atype acceptors (an acceptor other than the nitrogen of the oxime) functional group is made,taking into account their moieties. The majority of these oximes form dimeric, R22 (6),structures but R33 (8) and R44 (12) were also found. C3 chains which were classically claimedas the usual oxime H‐bond pattern were rarely observed. They are mostly found in aldoximestructures.